Cervical intraepithelial neoplasia in Peru Naval Medical Center. - Calderón Oblitas, David (2015)
We show in this paper, the Management of Cervical intraepithelial neoplasia (CIN) in Gynecologic Oncology Naval "CMST" Medical Center, in the last five years and their results. The scheme followed involves: Detections; 28 373% extended cytology (Pap), finding 291 Abnormal (PAP) were evaluated. For a diagnosis of CIN, and shall specify the grade, these 291 patients were subjected to the following sequence: Clinical Examination, anti-inflammatory treatment, colposcopy, Pap. Repeated, directed biopsy (Ex-Dr.) Endocervical curettage (ECC), Reeveluaciones, conization (in cases of unsatisfactory colposcopy) Final Histological Diagnosis: CIN I, II, III = 208; Ca 45 False invasive, Pap. Positive Impact of IAS 13. = = 68%. Directed Electrocauterization treated with 55 patients (24: 52%) with 92.16% cure controlled more than three years. 77 were treated with cone biopsy (37.07), obtaining a cure in 97.1%. Hysterectomy were treated with 80 (38.46%) to obtain a 100% cure. The results are comparable to those obtained in the best hospitals. This work has also served to point out the good correlation and diagnostic efficiency of our technique Colposcopy - Ex-Headed compared with that obtained by Cone (75.8%), better correlation cytology (Pap) - Cone 70%. Being the best resultadas when colposcopy practiced Ex-Dr., CEC and PAP. Avoiding Cone 74.6% for diagnostic purposes.